UAV/UAS Photogrammetry for Use in Cadastral Surveying - T. P. Kersten; F. Preuß; F. Preuß; D. Teten; M. Lindstaedt (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The potential of unmanned aerial vehicle (UAV) or unmanned aerial systems (UAS) photogrammetry for use in cadastral surveying tasks was explored as part of a research collaboration with the HafenCity University Hamburg and the Schleswig-Holstein State Office for Surveying and Geoinformation in Elmshorn, Germany. The building ensemble of a farm in Tensbüttel-Röst near Albersdorf, Germany was recorded with the DJI Phantom 4 Pro KlauPPK UAV system in various aerial flight configurations. The objective was to investigate and analyse the achievable geometric accuracy for a photogrammetric cadastral survey. The accuracy of the aerial triangulation was evaluated through the utilisation of diverse ground control point and check point configurations with the Agisoft Metashape software. The coordinates of the building were determined through the three different point measurement techniques. The roofscapes of the buildings and the 3D buildings were modelled as additional products. A digital orthophoto was also generated with the corresponding ground resolution. The accuracy, completeness and cost-effectiveness of the results of the UAV/UAS photogrammetry are discussed in comparison to the classical tachymetric building survey. It could be demonstrated that photogrammetric cadastral surveying is technically and economically feasible for building ensembles. However, the legal framework for this is not yet in place in some German federal states.